DIGITAL PUBLIC INFRASTRUCTURE FOR SUSTAINABLE DEVELOPMENT IN UTTARAKHAND: A CONCEPTUAL MODEL FOR AI-DRIVEN LOCAL GOVERNANCE AND E-GOVERNANCE - Tushar Dhiman; Pankaj Madan (International Educational Journal of Science and Engineering, 2025)
The integration of Artificial Intelligence with Digital Public Infrastructure represents a transformative pathway for enhancing local governance and promoting sustainable development, particularly in geographically complex and resource-sensitive regions such as Uttarakhand. This paper presents a conceptual framework that explores the synergies between AI and DPI to enable inclusive, transparent, and responsive governance models. Leveraging foundational platforms such as Aadhaar, UPI, DigiLocker, and BharatNet, DPI establishes a backbone for service delivery. When augmented with AI technologies like predictive analytics, natural language processing, and machine learning this digital infrastructure can significantly improve public administration, policy implementation, and citizen engagement. Uttarakhand, a Himalayan state characterized by dispersed populations, ecological fragility, and infrastructure gaps, requires adaptive and data-driven governance mechanisms. AI-powered e-governance has the potential to address these challenges by enabling real-time decision-making, participatory governance, and targeted delivery of essential services. This study constructs a conceptual model to highlight the interconnections between DPI, AI-enabled governance, and sustainable development outcomes across environmental, social, and economic domains. It also identifies critical feedback loops that support continuous improvement and inclusivity. The proposed model serves as a foundation for future empirical studies and policy initiatives aimed at leveraging AI and DPI to build a more equitable, efficient, and sustainable governance framework in Uttarakhand. This conceptual inquiry contributes to the broader discourse on digital transformation and sustainable development in the Indian context.